2005
DOI: 10.1007/s10488-004-1663-2
|View full text |Cite
|
Sign up to set email alerts
|

Crossing The Divide: Primary Care And Mental Health Integration

Abstract: This paper describes the views of primary care providers about treating depression among adult Medicaid patients and their experiences with managed behavioral health care. It also shows the outcomes of an intervention project that provides a care manager to facilitate connections among PCPs, patients, and behavioral health providers. Despite widespread initiatives to improve depression management in primary care and to manage behavioral health services, it appears that links between the two systems and the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, 61% of those who have CODs of both serious mental illness and a substance use disorder have not received treatment of either illness (SAMHSA, 2002). To complicate matters, individuals with CODs of mental illness and substance abuse have higher rates of chronic health problems (Dickey, Normand, Weiss, Drake, & Azeni, 2002;Upshur, 2005), have multiple rehospitalizations, frequently overutilize emergency services (Curran et al, 2003), and are frequently seen within the primary health care context (Gournay, Sandford, Johnson, & Thornicroft, 1997). Individuals with COD have higher morbidity and mortality rates when compared with the general population (Chafetz, White, Collins-Bride, & Nickens, 2005).…”
mentioning
confidence: 99%
“…Furthermore, 61% of those who have CODs of both serious mental illness and a substance use disorder have not received treatment of either illness (SAMHSA, 2002). To complicate matters, individuals with CODs of mental illness and substance abuse have higher rates of chronic health problems (Dickey, Normand, Weiss, Drake, & Azeni, 2002;Upshur, 2005), have multiple rehospitalizations, frequently overutilize emergency services (Curran et al, 2003), and are frequently seen within the primary health care context (Gournay, Sandford, Johnson, & Thornicroft, 1997). Individuals with COD have higher morbidity and mortality rates when compared with the general population (Chafetz, White, Collins-Bride, & Nickens, 2005).…”
mentioning
confidence: 99%
“…Hepner et al (2007) found that PCPs adhered to guidelines to a high degree in detecting and initiating treatment, but to a lower degree in further assessment of symptoms, adjustment of treatment, and follow-up to assure treatment completion. Upshur (2005) similarly reported on usual care described by Medicaid managed care PCPs, who reported using informal methods of assessment and diagnosis, with mostly pharmaceutical treatment, plus supportive visits, and referral to MH. Additionally, they noted the rarity of links between PC and MH.…”
Section: Discussionmentioning
confidence: 88%
“…But, recent studies that have described usual care by primary care providers (PCPs) have focused primarily on aspects of the process between an individual patient and provider (Hepner et al 2007;Robinson et al 2005;Solberg et al 2005;Upshur 2005), especially antidepressant prescribing and management (Joo et al 2005;Young et al 2001), or other specific aspects of care, such as diagnosis and treatment (Liu et al 2006). Other reports have described barriers to depression care (Nutting et al 2002;Pincus et al 2003) or barriers to implementing collaborative care models (Kilbourne et al 2004), but not the process of care, per se.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, references were located about integrating medical and behavioral health care. 14,15,16,17 An additional search of 345 references in PubMed using the term "care management initiatives mental health" revealed that such initiatives that are in place generally are supported by federal legislation. 18,19 However, none of these specifically identified the CCM.…”
Section: Literature Reviewmentioning
confidence: 99%